2007
DOI: 10.1111/j.1399-5618.2007.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

The nature of abnormal language processing in euthymic bipolar I disorder: evidence for a relationship between task demand and prefrontal function

Abstract: We have demonstrated abnormal prefrontal activation in bipolar patients across a range of language tasks with varying task demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 63 publications
2
25
2
1
Order By: Relevance
“…We could not verify a similar effect in our present sample, but we note that the region previously reported was centered in left dorsolateral prefrontal cortex and extended only marginally to the most apical part of Broca's area. Importantly for the specificity of our findings, neither that report [Curtis et al, 2007] nor an earlier one by our group [Curtis et al, 2001] found significant differences between bipolar subjects and controls in right inferior frontal areas. Current evidence, however, increasingly supports an overlap in genetic risk factors between schizophrenia and bipolar disorder [Cardno et al, 2002;Owen et al, 2007].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…We could not verify a similar effect in our present sample, but we note that the region previously reported was centered in left dorsolateral prefrontal cortex and extended only marginally to the most apical part of Broca's area. Importantly for the specificity of our findings, neither that report [Curtis et al, 2007] nor an earlier one by our group [Curtis et al, 2001] found significant differences between bipolar subjects and controls in right inferior frontal areas. Current evidence, however, increasingly supports an overlap in genetic risk factors between schizophrenia and bipolar disorder [Cardno et al, 2002;Owen et al, 2007].…”
Section: Discussioncontrasting
confidence: 65%
“…Because of a relative scarcity of functional neuroimaging studies in bipolar disorder, it is more difficult to place our results in context. However, using a similar overt letter fluency task in a sample of 12 bipolar subjects, Curtis et al [2007] found increased activation in left frontal areas for bipolar subjects relative to healthy controls. We could not verify a similar effect in our present sample, but we note that the region previously reported was centered in left dorsolateral prefrontal cortex and extended only marginally to the most apical part of Broca's area.…”
Section: Discussionmentioning
confidence: 94%
“…This has led to neurobiological theories that attribute cognitive deficits and emotional changes to a disconnect between cognitive top-down centers in the ventrolateral and dorsolateral PFC with emotional bottom-up centers in medial and orbitofrontal PFC and limbic regions (23, 24). Supporting these theories, fMRI studies of WM in inter-episode patients with BD have primarily found attenuated activation patterns in dorsolateral and ventrolateral PFC compared to healthy participants (21), though this is not always the case (25, 26). Additionally, studies demonstrate decreased activation in other brain regions underlying WM including the supramarginal gyrus (5).…”
mentioning
confidence: 98%
“…N = number in sample. BD = Euthymic bipolar patients; CON = Healthy comparison subjects; PFC = prefrontal cortex; ↑ = increase brain response in euthymic bipolar patients relative to healthy comparison subjects; ↓ = decrease brain response in euthymic bipolar patients relative to healthy comparison subjects; --- = no performance change or prefrontal region identified. Citations: Adler, Holland, Schmithorst, Tuchfarber, & Strakowski, 2004; Allin et al, 2010; Costafreda et al, 2009; Curtis et al, 2001; Curtis et al, 2007; Drapier et al, 2008; Frangou, Kington, Raymont, & Shergill, 2007; Glahn et al, 2010; Gruber, Rogowska, & Yurgelun-Todd, 2004; Hamilton et al, 2009; Hassel et al, 2008; Jogia, Dima, Kumari, & Frangou, 2011; Kaladjian et al, 2009; Kronhaus et al, 2006; Lagopoulos, Ivanovski, & Malhi, 2007; Lagopoulos & Malhi, 2007; Malhi, Lagopoulos, Owen et al, 2007; Malhi, Lagopoulos, Sachdev et al, 2007; Malhi et al, 2005; Monks et al, 2004; Pompei, Dima, Rubia, Kumari, & Frangou, 2011; Pompei, Jogia et al, 2011; Robinson et al, 2009; Robinson et al, 2008; Strakowski et al, 2005; Surguladze et al, 2010; Thermenos et al, 2010; Wessa et al, 2007; Yurgelun-Todd et al, 2000. …”
Section: Figurementioning
confidence: 99%